Michael Dummett on Analytical Philosophy - Szubka, Tadeusz (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The British philosopher Michael Dummett (1925–2011) not only had a massive influence on the development of analytical philosophy within philosophy of language, philosophy of mathematics, and metaphysics, but also contributed significantly to historical and metaphilosphical debates about the nature of this philosophical movement and its proper account. He proposed to define analytical philosophy as philosophy whose aim is the analysis of the structure of thought by way of the analysis of language. Hence, it is philosophy the gist of which is the linguistic turn. A number of critics of this proposal (including Barry Smith, Peter Hylton, and Hans-Johann Glock) emphasised that Dummett’s proposal captures merely some features of this diversified and multifaceted philosophical tradition, and is far from being historically adequate.